Receptor‐Level Proximity and Fastening of Ligands Modulates Stem Cell Differentiation (Adv. Funct. Mater. 30/2022). (25th July 2022) - Bae, Gunhyu; Kim, Myeong Soo; Thangam, Ramar; Koo, Thomas Myeongseok; Jang, Woo Young; Yoon, Jinho; Han, Seong‐Beom; Yang, Letao; Kim, Seong Yeol; Kang, Nayeon; Min, Sunhong; Hong, Hyunsik; et al.
Abstract : Integrin Clustering In article number 2200828, Young Keun Kim, Heemin Kang, and co‐workers report the dynamic tuning of receptor‐level ligand proximity. Closely spaced ligands coated onto subordinate nanostructures distributed on a nano‐template stimulate integrin binding and clustering. This activates the spreading, mechanotransduction, and differentiation of stem cells that occur in an active pro‐regenerative microenvironment.